Pengaruh Kompetensi Kepribadian Guru Pendidikan Agama Kristen Terhadap Minat Belajar Siswa Kelas VIII SMP Negeri 2 Porsea Kabupaten Toba Tahun Pembelajaran 2023/2024 (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to determine the positive and significant influence between the Personality Competencies of Christian Religious Education Teachers on the Learning Interest of Class VIII Students of SMP Negeri 2 Porsea, Toba Regency, Academic Year 2023/2024. The research method used is a quantitative method with a descriptive inferential type. The population is all 194 students of SMP Negeri 2 Porsea, Toba Regency, 2023/2024 academic year and a sample of 58 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 40 items, namely 23 items for variable Toba for the 2023/2024 Academic Year is shown through: 1) Test of analysis requirements: a) positive relationship test obtained by rxy = 0.802 > rtable (α=0.05; IK=95%; n=58) = 0.254. b) a significant relationship test is obtained from the value of tcount = 10.037 > ttable = 2.000. 2) influence test: a) regression equation test, obtained the regression equation Ŷ = 24.713 (α) + 0.456 (X). b) regression coefficient of determination test (r2) = 64.3%. 3) hypothesis testing using the F test obtained Fcount > Ftable=(α=0.05, dk numerator n-1=57, dk denominator=n-2=58-2=56) namely 100.739 > 1.555. Thus, H0 which states there is no influence is rejected and Ha which states there is an influence is accepted.